2002
DOI: 10.4049/jimmunol.168.10.4920
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of Chemokine Receptor Expression on Peripheral Blood γδ T Lymphocytes: Strong Expression of CCR5 Is a Selective Feature of Vδ2/Vγ9 γδ T Cells

Abstract: γδ T lymphocytes play an important role in the immune defense against infection, based on the unique reactivity of human Vδ2Vγ9 γδ T cells toward bacterial phosphoantigens. Chemokines and their corresponding receptors orchestrate numerous cellular reactions, including leukocyte migration, activation, and degranulation. In this study we investigated the expression of various receptors for inflammatory and homeostatic chemokines on peripheral blood γδ T cells and compared their expression patterns with those on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
153
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 143 publications
(163 citation statements)
references
References 55 publications
10
153
0
Order By: Relevance
“…Interestingly, it has been shown recently that granzyme A produced by adult Vγ9Vδ2 T cells, independently of perforin and granzyme B, induces macrophages to inhibit the growth of intracellular mycobacteria (77). Fetal Vγ9Vδ2 T-cell effectors expressed high levels of the inflammatory chemokine receptors CCR5 and CXCR3, which have been described as being particularly highly expressed on adult blood Vγ9Vδ2 T cells (78). Thus, it seems that this feature of adult Vγ9Vδ2 T cells, like other features, such as their high capacity to produce IFN-γ and granzymes A/K, already is programmed within the fetus rather than being a consequence of exposure to phosphoantigens after birth and associated differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, it has been shown recently that granzyme A produced by adult Vγ9Vδ2 T cells, independently of perforin and granzyme B, induces macrophages to inhibit the growth of intracellular mycobacteria (77). Fetal Vγ9Vδ2 T-cell effectors expressed high levels of the inflammatory chemokine receptors CCR5 and CXCR3, which have been described as being particularly highly expressed on adult blood Vγ9Vδ2 T cells (78). Thus, it seems that this feature of adult Vγ9Vδ2 T cells, like other features, such as their high capacity to produce IFN-γ and granzymes A/K, already is programmed within the fetus rather than being a consequence of exposure to phosphoantigens after birth and associated differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, pleural mesothelial cells are responsible in part for initiating the inflammatory response by recruiting mononuclear cells from the vascular compartment into the pleural space through chemokine receptors and their ligands [44]. A weak CCR7 expression in ex-vivo gdT cells from healthy individuals has been found, the majority being CD45RO + cells [45], and stimulation with heat-killed extracts of Mtb downmodulates CCR5 expression on gdT cells [45]. gdTCR triggering induces early and transient CCR7 up-regulation, regarded as a marker of early activation in these cells, together with high CXCR3 expression [46].…”
Section: Discussionmentioning
confidence: 99%
“…23,24 CCR5, a receptor for CCL3, CCL4 and CCL5 is strongly expressed on gd T cells compared with ab T cells. 25 Recently, it has been reported that CCL2, CCL3 and CCL5 play an essential role not only in inflammatory diseases but also in several cancers, suggesting that gd T cells could access to the tumor local sites directly without detouring around the lymph nodes. [23][24][25][26][27] In addition, Gong et al 28 reported that in vitro activation of Vg9Vd2 T cells by phosphoantigen and IL-2 down-regulated the IL-2-induced expansion of CD4 + CD25 + FoxP3 + regulatory T cells.…”
Section: Mage-a4-specific Abtcr-engineered CD T Cells a Hiasa Et Almentioning
confidence: 99%
“…25 Recently, it has been reported that CCL2, CCL3 and CCL5 play an essential role not only in inflammatory diseases but also in several cancers, suggesting that gd T cells could access to the tumor local sites directly without detouring around the lymph nodes. [23][24][25][26][27] In addition, Gong et al 28 reported that in vitro activation of Vg9Vd2 T cells by phosphoantigen and IL-2 down-regulated the IL-2-induced expansion of CD4 + CD25 + FoxP3 + regulatory T cells. It is also speculated that early IFN-g secretion through either ab or gd TCR enhances immunogenicity of tumors through mechanisms such as increased MHC expression on tumor cells, inhibit the induction of CD4 + CD25 + regulatory T cells and further promotes ab TCR recognition of target cells, 8,29,30 thus providing a positive feedback loop for anti-tumor immune responses.…”
Section: Mage-a4-specific Abtcr-engineered CD T Cells a Hiasa Et Almentioning
confidence: 99%